r 1985
DOI: 10.20955/r.67.12-20.xep
|View full text |Cite
|
Sign up to set email alerts
|

The New Bank Capital Adequacy Standards

Abstract: HE thi-ee federal agencies that regulate US, commercial banksthe Federal Deposit Insurance Corporation (FDIC), Federal Reserve FED) and Office of the Comptroller of the Currency (0CC)-recently adopted new capital adequacy standards for hank supervision and regulation purposes.' The new minimum standards are 5,5 percent for the ratio of primary capital to total assets and 6 percent fot-the ratio of total capital to total assets.' In general, the new standards increase the minimum capital requirements for larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…All three federal banking agencies limit the aggregate amount of secondary capital to less than 50 percent of the amount of a bank's primary capital. See Santomero [23] and Gilbert, Stone, and Trebing [7] for a discussion.…”
mentioning
confidence: 99%
“…All three federal banking agencies limit the aggregate amount of secondary capital to less than 50 percent of the amount of a bank's primary capital. See Santomero [23] and Gilbert, Stone, and Trebing [7] for a discussion.…”
mentioning
confidence: 99%
“…Since national banking law until the late 1980s only defined a minimum absolute level of required capital (rather than capital ratios), the individual federal regulatory authorities were dependent upon informal pressure to influence banks to maintain adequate capital levels: "...none of the regulators had formally stated minimum requirements for the ratio of total capital to total assets. Instead, each regulator typically compared capital ratios for banks grouped together by common characteristics, including asset size, and attempted to persuade those banks that had relatively low capital ratios to raise them" (Gilbert, Stone, and Trebing 1985).…”
Section: Weakness Of Minimum Capital Standardsmentioning
confidence: 99%
“…Studies commissioned in the 1960s and 1970s comparing the costs and benefits of membership in state versus national level regulatory regimes indicated that the costs of national regulation were considerably greater than the benefits in many states, which in addition to less rigorous capital standards often had lower minimum reserve requirements, cheaper deposit insurance programs, and laxer risk diversification standards. The possibility of "exit" to state-level systems to avoid the costs of federal regulation became known as the "membership problem" for the Federal Reserve System (Gilbert, Stone, and Trebing 1985).…”
Section: Weakness Of Minimum Capital Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed guideline would assign weights based on relative risk to assets and certain offbalance sheet items. The sum of these weighted asset values is the weighted risk asset total against which actual primary capital would be compared.°S ee Gilbert, Stone and Trebing (1985).…”
Section: Capital Adequacymentioning
confidence: 99%